Design of a Voice Based Intelligent Prototype Model for Automatic Control of Multiple Home Appliances - Olufisoye, Akanbi Caleb; O, Oladeji D. (Transactions on Engineering and Computing Sciences, 2016)
The revolution in Information Technology(IT) and Artificial Intelligent has provided innovations in diverse kinds of home automation where appliances can be controlled effortlessly and seamlessly .In this paper a review of several home automation technologies was presented and the advantages voice based technology was considered trending among other technologies in terms of flexibility and cost and comfort. In this paper, the conceptual prototype design model and the circuit diagram for controlling multiple home appliances at the same time were presented. The model uses Arduino Uno microcontroller system to control multiple home electrical or electronic appliances with maximum of 5 volts. The design transmits voice command through user wireless microphone (attached to the user cloth) to the intelligence micro controller via graphical user interphase (GUI). The control software developed for the prototype model was implemented using C# programming language, Microsoft Visual Studio.Net and Microsoft Speech recognition system.